Efeitos da acupuntura e da eletroacupuntura sobre o estresse oxidativo em ratos sadios - Silva, Agamenon Honorio (2009)
Acupuncture (Ac) is a form of therapy that seeks the cure of illnesses by applying stimuli through the skin by inserting needles at specific points called acupoints. Electro-acupuncture (EAc) is the application of electric current of low intensity and variable frequency to metal needles introduced into the body of the animal or human being. The insertion and manipulation of acupuncture needles cause cell damage at local level, leading to the production of biochemical substances, such as substance P, and transformation of arachidonic acid to leukotrienes, thromboxane types A2, B2 and prostaglandins PGE2, PGD2. The substance P, activates the mast cells, which release histamine by stimulating the C fibers and promoting vasodilation in the capillary level. The "oxidative stress" results from the imbalance between production and neutralization of free radicals derived from metabolic processes. The objective of this study was to evaluate the oxidative stress in organs (liver and kidney) and plasma of healthy rats subjected to manual and electrical stimulation applied in acupoints RM-12 (Zhongwan) and S-36 (Zusanli) bilaterally. Forty-eight rats were randomized into 4 groups (GVB, GAc, GEAc10 and GEAc100) and subjected to anesthesia trauma, followed by the application of acupuncture (GAc) and electroacupuncture (Geac 10 Hz and Geac 100 Hz) for 30 minutes . GVB group was used as control. At the end of 30 (T-30) and 60 (T-60) minutes arterial blood, liver and kidney samples were collected to determine the concentration of thiobarbituric acid reactive substances (TBARS) and reduced glutathione (GSH). In this study, the Ac did not significantly alter the concentration of MDA in plasma and liver of rats. However, in the kidney, there was a significant increase of lipid peroxidation in two time points (T-30: vs 0,050,01. 0.08 ± 0.03, p> 0.05 and T-60: 0.03 ± 0.01 vs. 0.07 ± 0.02, p> 0.05). The use of EAc (10 Hz) induced a significant increase in plasma MDA in the T-30 (0.02 ± 0.02 vs. 0.07 ± 0.02, p> 0.05) and liver of these animals in the T-60 (0.03 ± 0.03 vs. 0.12 ± 0.03, p> 0.01). The Ac promoted a significant increase in the concentrations of GSH in the liver of mice in the T-30 timepoint (7.58 ± 2.15 vs. 13.53 ± 0.80 **, p> 0.01).The EAc has promoted a significant increase of hepatic GSH concentrations in the T-30 (7.58 ± 2.15 vs. *** 17.54 ± 2.44, p> 0.001) and T-60 (8.09 ± 1 , vs. 93. 21:54 ± 2.71 ***, p> 0.001) timepoints in GEAc10 and T-30 (7.58 ± 2.15 vs. *** 24.15 ± 3.80, p> 0.001) and T-60 (8.09 ± 1.93 vs. *** 26.76 ± 2.52, p> 0.001) in Geac 100. Considering the results presented herein it is concluded that the use of acupuncture and electroacupuncture enhance lipid peroxidation in liver and kidney and promote a significant protective effect on oxidative stress in healthy rats.